Bond behavior of smooth and sand-coated shape memory alloy (SMA) rebar in concrete. (February 2016) - Muntasir Billah, A.H.M.; Alam, M. Shahria
Abstract: The distinct superelastic properties and flag shape hysteresis of shape memory alloys (SMAs) make them an ideal candidate for the design and development of various structural components in civil infrastructure. Due to the fact that SMA reinforcement has significantly different properties than conventional steel, structures reinforced with SMA will behave differently. The design equations used for steel reinforced concrete structures are not applicable while using SMA as reinforcement in concrete. This study investigated the bond behavior of SMA rebars (with and without sand coating) in concrete using 56 pushout specimens. The test results are explored to evaluate the influence of concrete strength, bar diameter, embedment length, and surface condition. Surface modification using sand coating notably improved the bond strength of SMA rebar. Finally, empirical equation based on statistical analyses is presented to predict the maximum average bond strength. The proposed equation reasonably calculates the average bond strength of SMA reinforcing bars in concrete.